Child Punishment between Incentive and Aggression From the Viewpoint of Mothers and Teachers - Mussa, Meyada Asaad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current research is to reveal whether the punishment of children is an incentive or an aggression from the viewpoint of their mothers and teachers. To achieve this, the scale was constructed which consist of (19) item that represent the behavior of mothers and teachers with their children, and the items were united by two main choices as: an incentive and an aggression (and both options consist of three alternatives: Considered incentive (large, medium, and weak) and Consider aggression (large, medium, and weak). The psychometric properties of the scale were verified by extracting the apparent validity and validity of the peripheral comparison, as well as the reliability of the test-retest method and it reached (88.0) for the paragraphs side when it is considered an incentive and (83.0) for the aspect of the paragraphs when it is considered aggression. The results showed that the teacher indicates that the punishment of children is an aggression rather than an incentive, and the vice versus for mothers.